Emergence of porcine-derived hybrid Escherichia coli with dual-disease manifestations in intestinal and extraintestinal niches - Xinming Pan; Jianan Liu; Zhonghao Chen; Caiying Li; Rong Chen; Zhen Zhang; Song Liang; Zongfu Wu; Huochun Yao; Jiale Ma (Virulence)
Escherichia coli, a significant zoonotic pathogen, continuously evolves to produce hybrid strains with diverse pathogenic characteristics, threatening public health. These hybrid strains are capable of causing multiple diseases across various tissues within a single host or among genetically diverse hosts. They have been reported to exhibit heightened virulence, enhanced infectiousness, and increased resistance to environmental clearance. Here, we identified a hybrid aEPEC/ExPEC isolate, PE164, from the bloody stool of a piglet with severe diarrhoea, which exhibited both intestinal and extraintestinal pathogenic traits. Monitoring the emergence of PE164-like hybrids in porcine-derived E. coli is crucial for animal production and public health safety. Phylogenetic and virulence gene analyses of nearly 300 clinical isolates from diseased pigs revealed eight hybrid strains categorized into four types, with significant variations in pathogenicity confirmed through in vitro and in vivo models. Notably, two O108 isolates, PE150 and PE164, were classified as highly virulent strains. A fused gene cluster involved in colanic acid and O108 antigen biosynthesis (CAO108) was identified as a key determinant of their extraintestinal pathogenicity, raising concerns about O-antigens linked to other exopolysaccharide components to generate new high virulence factors. Furthermore, the type III secretion system (T3SS), a classic pathway for pathogenic E. coli to optimally colonize the host gut, enhanced bacterial immune evasion and contributed to the extraintestinal pathogenicity of PE164. These findings underscore the prevalence of hybrid pathogenic E. coli strains in pigs, presenting new challenges for disease control.